Interferensi Morfosintaksis Bahasa Jawa oleh Penyiar Radio Saka FM Jogja - Maulana, Abang Muhammad Dalil (Crises on Languages and Literature, 2025)
This study aims to describe the forms and types of grammatical interference in Javanese into Indonesian. Twelve radio announcers' utterances were used as the subjects of the study. The method used in this study is a descriptive method with a qualitative research form, and uses a sociolinguistic approach. Data were taken from the utterances of Saka FM Jogja radio announcers. The results of this study analysis revealed several sentences containing grammatical interference. Grammatical interference is divided into sentences containing morphological interference and sentences containing syntactic interference. The form of morphological interference is divided into morphological interference formed by affixes, suffixes, and prefixes. The form of syntactic interference is divided into word formation interference, clause structure interference, and functional word interference.